Exergoeconomic analysis of a reversible solid oxide cell-based power-to-syngas-to-power system - Agbaje, Muiz Adekunle; Akkaya, Ali Volkan (INDERSCIENCE ENTERPRISES LTD, 2023)
This study investigates exergoeconomic performance of a power-to-syngas-to-power system based on a reversible solid oxide cell (ReSOC). Specific exergy cost (SPECO) approach is used for developing thermoeconomic model and power to syngas (SOEC) and syngas to power (SOFC) modes of ReSOC system are analysed. The results showed a capital cost rate of $9.25/h for the SOFC mode and $9.14/h for the SOEC mode of operation. The combined capital cost of storage tanks and ReSOC stacks accounts for approximately 80% of overall capital costs in both modes. Additionally, the cost of electricity significantly influences exergoeconomic performance. SOEC mode had a higher system exergy cost rate of $14.27/h, and SOFC mode had an exergoeconomic performance of 0.67. In conclusion, the exergoeconomic analysis has revealed the cost rates in the ReSOC system. These results would guide in determining the most effective points of cost reduction to improve economic performance of ReSOC-based system.
Keywords: cost analysis; energy storage; exergoeconomics; reversible solid oxide cell; SPECO; system analysis; ENERGY-STORAGE; PERFORMANCE ANALYSIS; MODEL VALIDATION; LEVELIZED COST; OPTIMIZATION; DESIGN; HYDROGEN; EXERGY; CYCLE; DRIVEN; Thermodynamics; Energy & Fuels